Assessment of hypolipidemic and anti‐inflammatory properties of walnut (Juglans regia) seed coat extract and modulates some metabolic enzymes activity in triton WR‐1339‐induced hyperlipidemia in rat kidney, liver, and heart. Issue 3 (29th December 2022) - Palabıyık, Esra; Sulumer, Ayşe Nurseli; Uguz, Handan; Avcı, Bahri; Askın, Seda; Askın, Hakan; Demir, Yeliz
Abstract: Atherosclerosis and cognitive impairment are both influenced by hyperlipidemia. Due to their high margin of safety and low cost, natural chemicals have recently attracted particular attention in the context of the treatment of disease. Hence, the purpose of this study was to investigate the possible amendatory impact of ethanol extract walnut ( Juglans regia ) seed coat (E‐WSC) on some metabolic enzymes (glutathione reductase (GR), paraoxonase‐1 (PON1), aldose reductase (AR), sorbitol dehydrogenase (SDH), acetylcholinesterase (AChE), glutathione S‐transferase (GST), and butyrylcholinesterase (BChE)) activity in the liver, kidney, and heart of rats with Triton WR‐1339‐induced hyperlipidemia. Rats were divided into five groups: control group, HL‐Control group (Triton WR‐1339 400 mg/kg, i.p administered group), E‐ WSC + 150 (150 mg/kg, o.d given group), E‐ WSC + 300 (E‐ WSC 300 mg/kg, o.d given group) and HL+ E‐WSC + 300 (Group receiving E‐ WSC 300 mg/kg, o.d 30 min prior to administration of Triton WR‐1339 400 mg/kg, i.p). In HL‐Control, AR, SDH, and BChE enzyme activity was significantly increased in all tissues compared to the control, while the activity of other studied enzymes was significantly decreased. The effects of hyperlipidemia on balance were improved and alterations in the activity of the investigated metabolic enzymes were prevented by E‐WSC. As a result, promising natural compounds that can be used as adjuvant therapy in the treatment of cognitive disorders and hyperlipidemia may be found in E‐WSC powder.